PENERAPAN METODE GLOBAL DALAM MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN BAHASA INDONESIA SISWA KELAS III UPT SPF SDN PANNARA KOTA MAKASSAR - Aulia Khaerunnisa; Tasrif Akib; Amal Akbar (STKIP Subang, 2025)
Aulia Khaerunnisa. 2025. Improving Reading Skills through the Global Method for Third Grade Students of UPT SPF SD Negeri Pannara Makassar City. Undergraduate Thesis. Department of Primary School Teacher Education, Universitas Muhammadiyah Makassar. Supervisor I: Tasrif Akib, Supervisor II: Amal Akbar. This study aims to improve the reading comprehension skills of third grade students at UPT SPF SD Negeri Pannara Makassar City through the implementation of the global method. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 26 third grade students in the 2025/2026 academic year. Data were collected through learning achievement tests and observation sheets, then analyzed both quantitatively and qualitatively. The results showed an improvement in students’ reading comprehension after the application of the global method. In the first cycle, most students were still categorized as low to moderate, and the mastery percentage did not meet the expected target. However, in the second cycle, a significant improvement occurred, with 88% of students achieving a score above 75 in accordance with the Minimum Mastery Criteria (KKM). This finding proves that the global method is effective in helping students understand reading materials gradually, starting from sentences, words, syllables, to letters, thereby facilitating a comprehensive understanding of the text. Thus, the application of the global method can be used as an alternative learning strategy in teaching Indonesian language to effectively improve elementary school students’ reading comprehension skills.